Penilaian Potensi Daya Tarik Wisata Alam Bahoan Nagori Dolok Marawa Kecamatan Silou Kahean Kabupaten Simalungun - Meylida Nurrachmania; Rozalina; Sarintan E Damanik; Triastuti; Marulam MT Simarmata (Jurnal Pengabdian Masyarakat Sapangambei Manoktok Hitei, 2022)
One of the wealth that Indonesia has is the wealth of tourist attractions. And the majority are nature-themed attractions. Kawah Putih Tinggi Raja, is one of the nature-themed tourist attractions that is hundreds of years old, located in the area of Dolok Tinggi Raja Nature Reserve Bahoan Nagori Dolok Marawa Village, Silau Kahean District, Simalungun Regency. In order to find out the natural tourism potential of the Tinggi Raja area, it is necessary to carry out practical assessment activities for the Tinggi Raja natural tourism area. In the discussion with the Focus Group Disscusion (FGD) model, various information emerged from the training participants in exploring the potential of nature that can be used as a tourist attraction in Nagori Dolok Marawa. Furthermore, it is assessed the potential of these natural tourism to be packaged as part of the Tinggi Raja natural tourism